Response of natural forest regeneration to human disturbance in Banke National Park - Napit, R.; Paudel, P. K. (Banko Janakari, 2015)
Tropical forest continues to decline in Nepal’s lowlands, with a serious negative consequence for biodiversity conservation. Even a strict natural reserve is subjected to have some degree of human disturbances. The newly established Banke National Park of Nepal provides an excellent context to evaluate effects of human disturbances on the forest regeneration status. This article assesses the regeneration status of the park. A total of 1,067 plots were laid out within the park area. In each plot, three concentric rings of radii of 10 m, 5 m, and 1 m were established. Data of seedling/sapling and human disturbance variables were collected from each of the concentric plots. Principal component analysis (PCA) of all disturbance variables was carried out to generate a disturbance index. The findings of this study alienates with intermediate disturbance hypothesis. Cut wood, lopped tree, human/livestock trails, people number - are the significant variables for the impact of sapling and seedling density in the park. The induced human disturbances up to the limit avails the highest regeneration status in the park. These human disturbances might have induced the spatial heterogeneity and internal dynamics which help in the regeneration. The main challenge for the forest managers and scientists is to identify the indicators of environmental damage of forest and their threshold levels at which human disturbances will result in an irreversible decline of the vegetation and its regeneration. Banko Janakari, A Journal of Forestry Information for Nepal Vol. 25, No. 1 Page: 39-49